A hybrid data analytic methodology for 3PL transportation provider evaluation using fuzzy multi-criteria decision making - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
Third-party logistics (3PL) service provider selection for a strategic alliance is not an easy decision, and is constantly associated with uncertainty and complexity. For this reason, in this study, a hybrid fuzzy multi-criteria decision-making methodology is proposed to provide a systematic decision support tool for 3PL provider evaluation, especially for 3PL transportation provider. The proposed evaluation methodology consists of several steps. First, the strategic goal and sub-attributes are identified for 3PL service provider evaluation. After constructing the hierarchy, Buckley's fuzzy-analytical hierarchy process (AHP) extension algorithm is used to determine the evaluation criteria weights. Then, by using fuzzy-AHP results as input weights, the fuzzy-Technique for Order Preference by Similarity to Ideal Solution technique is conducted in order to identify the most suitable third-party providers. Finally, a real-life case study in a confectionary company is presented to demonstrate the potential use of the methodology and a sensitivity analysis is performed to analyse the hybrid methodology proposed here. In the conclusion of the study, future recommendations are presented.
Keywords: 3PL transportation; supplier selection; business analytics; fuzzy-AHP; fuzzy-TOPSIS; multi-criteria decision making; EXTENT ANALYSIS METHOD; 3RD-PARTY LOGISTICS; TOPSIS MODEL; SELECTION; AHP; ALTERNATIVES; INDUSTRY; GOALS